Central Hypoventilation Is a Key Risk Factor for Mechanical Ventilation During the Acute Phase of Anti-N-Methyl-D-Aspartate Receptor Encephalitis - Xu, Qianhui; Wang, Qian; Han, Jing; Mao, Fengju; Zeng, Silin; Chen, Siyan; Zhao, Chenyong; Gu, Mei; Li, Zaiwang; Fu, Xuejun; Luo, Xiaoguang; Huang, Ying (Frontiers in Neurology, 2021)
Objective: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is an acute form of encephalitis of autoimmune etiology. We aimed to evaluate the risk factors that predicted the need for mechanical ventilation during the acute phase of anti-NMDAR encephalitis through an analysis of the clinical characteristics and biochemical test results of the patients with anti-NMDAR encephalitis. Methods: In this retrospective study, patients who primarily presented with anti-NMDAR encephalitis and exhibited anti-NMDAR antibody positivity in the cerebrospinal fluid between November 2015 and February 2020 were included. Data on the clinical characteristics, biochemical test results, and treatment methods selected for the patients were collected for the analysis of factors predicting the need for mechanical ventilation. Results: Thirty-one patients with a median age of onset of 31 years (inter-quartile range: 21–48 years) were included in this study, of which 15 were male (48.4%). Psychosis (23, 74.2%), seizures (20, 64.5%), and memory deficit (20, 64.5%) were the most common clinical manifestations. At admission, 17 patients (54.8%) presented with pyrexia, of which 12 (38.7%) had a body temperature ≥ 38°C, and 6 patients (19.4%) presented with central hypoventilation. All patients received first-line therapy (glucocorticoids, intravenous immunoglobulin or plasmapheresis alone or combined), whereas 2 patients (6.5%) received rituximab, a second-line agent, as well. Seven patents required mechanical ventilation. Results of univariate logistic regression analysis revealed that body temperature ≥ 38°C (odds ratio [OR] = 18, 95% confidence interval [CI]: 1.79–181.31, P < 0.05) and central hypoventilation at admission (OR = 57.50, 95% CI: 4.32–764.89, P < 0.05) were the risk factors for mechanical ventilation. Multivariate logistic regression analysis showed that central hypoventilation at admission was the only risk factor predicting the need for mechanical ventilation. Conclusion: Central hypoventilation at admission is a key risk factor for mechanical ventilation during hospitalization in patients with anti-NMDAR encephalitis.